2019
DOI: 10.1039/c8ce01988f
|View full text |Cite
|
Sign up to set email alerts
|

Improved crystal quality of non-polar a-plane GaN epi-layers directly grown on optimized hole-array patterned r-sapphire substrates

Abstract: The characteristics of a-plane GaN films directly grown on silicon dioxide (SiO2) hole-array patterned r-sapphire substrates (HPSS) were investigated in this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The XRC ω-scan was performed at phi angle intervals of 30°, where the X-ray beam was placed parallel to the c - and m -axes along the (11–20) plane at 0° and 90° phi angles, respectively. The FWHM plot exhibits the same trend as the nonpolar XRC measurements, that is, the anisotropy of nonpolar GaN results in an “M”-shaped plot with respect to the phi angle 10 , 15 , 31 . The lowest FWHMs are observed at a phi angle of 0°, corresponding to 1224, 1044, 864 and 756 arcsec for samples S1, S2, S3 and S4, respectively.…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…The XRC ω-scan was performed at phi angle intervals of 30°, where the X-ray beam was placed parallel to the c - and m -axes along the (11–20) plane at 0° and 90° phi angles, respectively. The FWHM plot exhibits the same trend as the nonpolar XRC measurements, that is, the anisotropy of nonpolar GaN results in an “M”-shaped plot with respect to the phi angle 10 , 15 , 31 . The lowest FWHMs are observed at a phi angle of 0°, corresponding to 1224, 1044, 864 and 756 arcsec for samples S1, S2, S3 and S4, respectively.…”
Section: Resultsmentioning
confidence: 53%
“…Note that the anisotropy of nonpolar GaN induces orthorhombic distortion in the grown a -GaN 11 , 15 , 34 . The asymmetric crystal arrangement consequently distorts the wurtzite structure 18 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This minimum BSFD is quite remarkable compared to that currently reported for m-plane AlN and a-plane GaN (BSFD ∼ 5000 cm −1 ). 11,26 The representative works on nonpolar AlN fabricated on the sapphire substrates are listed in Table 2, in which the FWHMs and BSFDs are used to reflect the crystal quality of the nonpolar AlN samples.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, (1120)-plane nonpolar GaN film was successfully grown on a (0001)-plane sapphire substrate using pulsed laser deposition (PLD) technology [36]. It was reported that the crystalline quality of nonpolar GaN could be improved by introducing a patterned SiO 2 layer [37]. However, the introduction of secondary epitaxy processes or growth techniques that are not entirely based on the metal organic chemical vapor deposition (MOCVD) system is detrimental to commercialization.…”
Section: Introductionmentioning
confidence: 99%